2022
DOI: 10.1111/bph.15965
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant branched‐chain amino acid accumulation along the microbiota–gut–brain axis: Crucial targets affecting the occurrence and treatment of ischaemic stroke

Abstract: Background and Purpose Although increasing evidence illustrated that the bidirectional communication between the brain and the gut is closely related to the occurrence of various complex diseases. Limited effort has been made to explore the influence of intestinal flora on the risk of ischaemic stroke. The present study aims to identify microbiota and specialized microbiota metabolites related to the occurrence and treatment of ischaemic stroke. Experimental Approach The role of microbiota in the occurrence an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 69 publications
4
14
0
Order By: Relevance
“…Note that rat studies have found a relationship between aberrant branched-chain amino acid metabolism and ischemic stroke. This relationship was due to a dysregulation of the microbiota-gutbrain axis (36). No such mechanism associating BCAA and microbiota has yet been reported for aSAH and DCI, but our finding that BCAA metabolism is linked to microbiota metabolism potentially involving bacterial species is consistent with (36).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Note that rat studies have found a relationship between aberrant branched-chain amino acid metabolism and ischemic stroke. This relationship was due to a dysregulation of the microbiota-gutbrain axis (36). No such mechanism associating BCAA and microbiota has yet been reported for aSAH and DCI, but our finding that BCAA metabolism is linked to microbiota metabolism potentially involving bacterial species is consistent with (36).…”
Section: Discussionsupporting
confidence: 66%
“…This relationship was due to a dysregulation of the microbiota-gutbrain axis (36). No such mechanism associating BCAA and microbiota has yet been reported for aSAH and DCI, but our finding that BCAA metabolism is linked to microbiota metabolism potentially involving bacterial species is consistent with (36). Most previous studies on aSAH and DCI have focused on brain metabolic issues.…”
Section: Discussionsupporting
confidence: 63%
“…Restoration of the L. helveticus and L. brevis colonies had strong neuroprotective effects. It significantly alleviated the accumulation of branched-chain amino acids (BCAAs), which aggravated microglia-induced neuroinflammation through the AKT/STAT3/NF-kB signaling pathway in the development of IS (Shen et al, 2023). Additionally, as an aged biome can increase the systemic proinflammatory cytokine levels (Spychala et al, 2018), which in turn contributes to the pathogenesis of IS, replenishing the gut microbiome with fresh microorganisms can reverse agerelated poor stroke recovery through host immunologic, microbial, and metabolomic modulation.…”
Section: Fecal Microbiota Transplantation (Fmt) In Ismentioning
confidence: 99%
“…Therefore, many researchers are investigating novel approaches for treating IS. In the past two decades, more than 1,000 potential neuroprotectants have been found to attenuate ischemic brain injury by promoting neuronal survival, neural plasticity, neurogenesis, and synaptogenesis (Liberale et al, 2018;Shen et al, 2023). However, the studies were mainly conducted on experimental IS animal models, and only a few agents targeting these molecules could be administered in the clinic (Gauberti et al, 2018;Gan et al, 2020;Mani et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…GM could influence neuropsychiatric disease, such as Alzheimer's disease, Parkinson's disease, depression, and AIS. The correlation between ischemic stroke and GM is widely concerned [9]. A large number of evidences showed the link between GM and AIS.…”
Section: Introductionmentioning
confidence: 99%